First insights on the presence of the unfolded protein response in human spermatozoa - Santiago, Joana (2019)
The unfolded protein response (UPR) is involved in protein quality control and is activated in response to several stressors. Although in testis the UPR mechanisms are well described, their presence in spermatozoa is contentious. We aimed to investigate the presence of UPR-related proteins in human sperm and the impact of oxidative stress induction in UPR activation. To identify UPR-related proteins in human sperm, a bioinformatic approach was adopted. To explore the activation of UPR, sperm were exposed to hydrogen peroxide (H2O2) and motility, vitality, and the levels of UPR-related proteins were assessed. We identified 97 UPR-related proteins in human sperm and showed, for the first time, the presence of HSF1, GADD34, and phosphorylated eIF2α. Additionally, the exposure of human sperm to H2O2 resulted in a significant decrease in sperm viability and motility and an increase in the levels of HSF1, HSP90, HSP60, HSP27, and eIF2α; all proteins involved in sensing and response to unfolded proteins. This study gave us a first insight into the presence of UPR mechanisms in the male gamete. However, the belief that sperm are devoid of transcription and translation highlight the need to clarify if these pathways are activated in sperm in the same way as in somatic cells.